Critiques and Challenges to Old and Recently Proposed American Psychiatric Association's Website DSM 5 Diagnostic Criteria for Sexual Dysfunctions - (:unkn) unknown (KURE ILETISIM GRUBU A S, 2013)
All the DSM classifications until present time based definitions of sexual dysfunctions on expert opinions that were not supported by sufficient clinical or epidemiological data. Additionally, older definitions of sexual dysfunctions (SD) included vague terms such as satisfactory, soon after, rapid, short, minimal, recurrent and persistent which were not precise and difficult to interpret. The DSM 5 attempted to operationalize the diagnostic criteria and avoided these vague terms. It also used specific duration and severity criteria to identify more homogeneous groups for purposes of good clinical epidemiological research and better treatment decisions. All of the DSM classifications until DSM 5 classified male and female SD on the same continuum based on unified sexual response cycles. DSM 5 made a major conceptual change and emphasized that different genders' sexual disorders are no longer required to be analogous. DSM 5 also merged female desire and arousal diagnosis into one entity defined as female sexual interest and arousal disorders. This paper aims to compare and contrast proposed APA website DSM 5 definitions of SD with that of DSM IVTR and explains the rationale for making these changes. It subsequently challenges the suggested DSM 5 criteria and addresses some issues to be considered further for future diagnostic criteria.
Keywords: Sexual dysfunction; diagnostic criteria; operational criteria; critiques and challenges; DSM 5; LIFELONG PREMATURE EJACULATION; MALE ORGASMIC DISORDER; ERECTILE DYSFUNCTION; RAPID EJACULATION; DESIRE DISORDER; DEFINITION; AROUSAL; WOMEN; CLASSIFICATION; EXPERIENCE